El expediente Lamborghini - Nieves Battistoni (Cuadernos LIRICO)
This article aims to investigate the incidence of unrestricted access to the archive in Ricardo Strafacce's biographical writing on Osvaldo Lamborghini, bearing in mind that the form of this biography corresponds to the Anglo-Saxon orthodox model. Telling a life in great dimensions, chronologically and monumentally, in the XXI century, perhaps it can be re-signified as an extremely adventurous gesture that approaches, in more than one sense, the "adventure of form" typical of the “biographies of the process ” (Pereira 2018). Derived from this, in a second moment, it is interesting to delve into the tension between biography and history as the author himself attributes the category of "Book of History of Argentine Literature". The historicizing desire that, I argued on another occasion, intimates with the purpose of eroding the myth of Lamborghini's cursed writer, composes a “expedient biography” in which the biographer-lawyer exercises his defense.